The book value of monetary gold - MACHLUP, F. (PSL Quarterly Review, 2014)
The debate over a devaluation of the U.S. dollar in terms of gold had been going on for months, but the parties seem to be unable to sort out sense from nonsense, truth from fiction, economics from politics and cosmetics. There is speak of “burden” and “burden sharing” where no economic loss or disadvantage is involved, and the dollar price of monetary gold is spoken of when neither a price nor an exchange value is involved but only a book value. The chief purpose of the present article is to clarify the issues rather than to make policy recommendations or predictions. However, in discussing the major arguments for and against an early change in the dollar valuation of gold, the author shows the strengths and weaknesses of the two positions. JEL: E40, E42